(untitled) (Research, Society and Development, 2021)
This study aimed to assess the reproducibility of linear measurements performed in dental models produced via intraoral scanning and three-dimensional (3D) printing using digital light processing (DLP) and fused deposition modeling (FDM). A sample of 22 participants was selected for this study. Intraoral scanning was performed in each participant with TRIOS™ (3Shape A/S™, Copenhagen, Denmark) device. The digital models were 3D printed using DLP and FDM techniques. Using a caliper, intraoral linear measurements were performed in situ (on the surface of participant’s teeth) and on the 3D printed models. The measurements taken intraoral and on the models were compared using the Intraclass Correlation Coefficient (ICC). The correlation between measurements taken in situ and on DLP models was poor (<0.4), while between in situ and FDM it ranged from poor to satisfactory (<0.75). Generalized linear model showed that the differences did not reach statistically significant levels (p>0.05). According to Bland-Altman approach, the size of measurements did not bias the outcomes. The intraoral scanning and 3D printing techniques used in this study enabled the reproducibility of linear measurements, however, discrete distortions that might be clinically significant occurred.